Serum Urotensin II Levels in Patients with Non-Dipper Hypertension. (November 2013) - Erbay, Ali Riza; Meric, Murat; Alacam, Hasan; Zengin, Halit; Akin, Filiz; Okuyucu, Ali; Yuksel, Serkan; Soylu, Korhan; Gedikli, Omer
<x xml:space="preserve">Abstract</x> Hypertension terms "dipper" and "non-dipper" are propounded by the change that occurs during ambulatory blood pressure (BP) monitoring. The purpose of this study is to present whether the serum urotensin II levels are different in patients with dipper and non-dipper hypertension and to put forward the effects causing this difference, if there are any. Patients recently diagnosed with hypertension were included in the study. With ambulatory BP monitoring, 81 patients with high BP were divided into two groups, dipper (n = 40) and non-dipper (n = 41). Serum urotensin II levels were analyzed by ELISA method. Serum urotensin II levels were higher in patients with non-dipper hypertension than in patients with dipper hypertension (204 [106–533] vs. 140 [96–309], P = .004). There was a positive correlation between total systolic BP and serum urotensin II levels (r = 0.408 and P = .009), but the relation in the non-dipper hypertension group was not significant (r = 0.194 and P = .2). In conclusion, serum urotensin II levels were higher in non-dipper HT patients than dipper HT patients. This higher urotensin II level might be responsible for poor prognoses.